2015
DOI: 10.1002/cam4.514
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate antigen 19‐9 is a useful prognostic marker in esophagogastric junction adenocarcinoma

Abstract: The incidence rate of esophagogastric junction (EGJ) adenocarcinoma has been rapidly increasing worldwide. Carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9) are major serum tumor markers in gastrointestinal cancers. However, the role of these markers in EGJ adenocarcinoma has not been thoroughly investigated. A total of 211 patients with EGJ adenocarcinoma who underwent surgery or endoscopic submucosal dissection at two academic institutions, Kumamoto University Hospital or Kyushu Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…Moreover, this autoantibody panel potentially demonstrated a better diagnostic sensitivity for early stage EJA patients than markers CEA and CA19-9, which are major serum tumor markers in gastrointestinal cancers currently used in clinical practice. The positive rates of CEA and CA19-9 in EJA patients were reported to be only 20.3% and 12.9%, respectively, and these markers are elevated most commonly in advanced-stage patients [ 37 ]. Furthermore, PPV is very important for a test used in early detection of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this autoantibody panel potentially demonstrated a better diagnostic sensitivity for early stage EJA patients than markers CEA and CA19-9, which are major serum tumor markers in gastrointestinal cancers currently used in clinical practice. The positive rates of CEA and CA19-9 in EJA patients were reported to be only 20.3% and 12.9%, respectively, and these markers are elevated most commonly in advanced-stage patients [ 37 ]. Furthermore, PPV is very important for a test used in early detection of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the current literature, risk factors for tumor recurrence such as an increased ASA-score, elevated levels of CA 19-9, or an advanced tumor stage have been described [11,[25][26][27][28][29]. Whether postoperative complications like anastomotic leakage affect the incidence of tumor relapse is discussed controversially [12,13].…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have shown that, CA125 was associated with the R0 resection rate [13], recurrence, peritoneal dissemination [14] and OS in unresectable advanced or recurrent GC patients [15]; CA199 was related to pN [7,[16][17][18] and pTNM stage [17]; and CA724 was related to the pathological stage and had a good diagnostic value for gastric cancer [19]. However, none of the patients in those studies underwent NCT.…”
Section: Discussionmentioning
confidence: 96%
“…Serum tumor markers play important roles in the diagnosis, prognostic prediction and recurrence monitoring of gastrointestinal malignancies. As studies have suggested, AFU was considered to be related to liver metastasis in colorectal cancer [4]; AFP was associated with prognosis in gastric cancer patients undergoing surgery alone [5]; preoperative CEA could predict the prognosis of GC patients with no lymph node metastasis [6]; CA199 was an independent prognostic factor in gastroesophageal junction (GEJ) cancer patients who experienced surgery alone [7]; the CA125 level was related to the degree of peritoneal dissemination and the existence of malignant ascites in GC patients with peritoneal metastasis [8]; and CA724 was correlated with pTNM stage in gastric carcinoma patients [9]. However, for GC patients who underwent NCT, the evidence of these markers is still insu cient.…”
Section: Introductionmentioning
confidence: 99%